Transformational Leadership Strategies in Improving Sustainable Healthcare - Vinanda, Firda; Wasiyem; Andini; Syafitri, Winda; Salwa Mut'hia Siregar; Muhammad Raihan Pratama (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Sustainable healthcare is becoming increasingly important in this modern era. Transformational leadership is expected to play a key role in achieving these goals. This study uses the Literature Review method by collecting data from various accredited sources such as journals, books, and online articles. The criteria used included literature published in the last five years (2020-2024) and the relevance between keywords and results. The literature search was carried out by four methods: Search Strategy, Selection Criteria, and Quality Assessment. The results of the study show that transformational leadership strategies have a significant positive impact on the sustainability of health services. By blending dimensions in transformational leadership, organizations can improve operational efficiency, drive innovation, and build long-term commitment from the workforce. This research emphasizes that transformational leadership is an important holistic approach in encouraging the sustainability of health services in the modern era.